Mitigating the risk of COVID-19 exposure by transitioning from clinic-based to home-based immune globulin infusion. (22nd February 2021) - Perreault, Sarah; Schiffer, Molly; Clinchy-Jarmoszko, Virginia; Bocchetta, Nicole; Barbarotta, Lisa; Abdelghany, Osama; Foss, Francine; Huntington, Scott; Seropian, Stuart; Isufi, Iris
Abstract: Purpose: Intravenous immune globulin (IVIG) therapy is used in patients with hypogammaglobulinemia to lower the risk of infections. IVIG and subcutaneous IVIG (SCIG) therapy have been to shown to be safe and effective when administered as clinic-based infusions. Concern from both patients and providers for increased transmission of the coronavirus disease 2019 (COVID-19) virus to immunosuppressed patients with scheduled medical visits and procedures made it necessary for us to reassess our process of how we manage patient care in general and chronic clinic infusions in particular. Here we describe our experience of transitioning patients from clinic-based to home based IVIG and/or SCIG infusions to decrease the risk of COVID-19 exposure. Methods: Criteria were developed to identify high-risk immunosuppressed patients who would be appropriate candidates for potential conversion to home based IVIG infusions. Data were collected via chart review, and cost analysis was performed using Medicare Part B reimbursement data. A patient outcome questionnaire was developed for administration through follow-up phone calls. Results: From March to May 2020, 45 patients met criteria for home-based infusion, with 27 patients (60%) agreeing to home-based infusion. Posttransition patient outcomes assessment, conducted in 26 patients (96%), demonstrated good patient understanding of the home-based infusion process. No infusion-related complications were reported, and 24 patients (92%) had no concerns about receiving future IVIG and/or SCIG doses at home. No patient tested positive for COVID-19 during the study period. Clinic infusion visits decreased by 26.6 visits per month, resulting in a total of 106 hours of additional available infusion chair time per month and associated cost savings of 12, 877. Conclusion: Transition of clinic based to home based IVIG/SCIG infusion can be successfully done to decrease potential exposure during a pandemic in a high-risk immunosuppressed population, with no impact on patient satisfaction, adherence, or efficacy. The home-based infusion initiative was associated with a reduction in costs to patients and an increase in available chair time in the infusion clinic.